STRATEGI PENCEGAHAN DAN PENANGANAN STUNTING DENGAN PENDEKATAN PENTAHELIX BERBANTUAN ANALYSIS HIERARCHY PROCESS DI KECAMATAN SERAM BARAT - Bertje Akollo; Stanislaus Kostka Ohoiwutun; Hendry Selanno (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2026)
This study aims to formulate a strategy for preventing and handling stunting with a pentahelix approach assisted by analysis hierarchy process in West Seram District. This study was designed in a quantitative form and used a survey method. The respondents of this study consisted of officers involved in the strategy for preventing and handling stunting in West Seram District, as many as 5 academics from the field of social welfare science and the field of public administration as many as 5 people, stunting observer communities as many as 2 people, the government (1 Health Office and 1 Bappeda) and 2 information media. . The data analysis used was AHP analysis which is an analysis method used to determine the priority order of a plan. The results of the study concluded that preventing and handling stunting in West Seram District requires a holistic and strategic approach, considering the complexity of the challenges faced. Weaknesses such as ineffective coordination, inaccurate data, and low public awareness must be addressed immediately through short-term strategies such as strengthening multi-sectoral cooperation, public awareness campaigns, and data updates. These steps will provide a strong foundation for broader interventions, while increasing public participation in supporting stunting programs. Cross-sector collaboration involving the media, celebrities, the private sector, and local communities is also key to driving rapid and effective behavioral change.